(untitled) (Foro de Educacion, 2026)
This study aims to address the challenges in physics experiment courses at universities in Xizang, including students’ insufficient foundational knowledge, a monotonous teaching mode, and limited teaching resources, through targeted teaching innovations to enhance learning outcomes. A mixed-methods approach combining action research and a case study was employed. The teaching reforms were implemented across the college physics experiment course at Xizang University. The innovations encompassed comprehensive reforms spanning course content, teaching methods, the learning environment, and the evaluation system. The effectiveness was evaluated through a questionnaire survey administered to a cohort of 65 students enrolled in the course, supplemented by a comparative analysis of teaching records before and after nearly three years of reform practice. Quantitative and qualitative analyses demonstrated remarkable results. Students’ final exam scores significantly increased from a pre-reform average of 66.96 to a post-reform average of 87.0. Questionnaire results indicated that student satisfaction ratings across all reform dimensions ranged from 4.25 to 4.43 (on a 5-point Likert scale). One-sample t-tests confirmed that all ratings were significantly above the neutral level (p < .001). The reforms effectively stimulated students’ learning interest and enthusiasm and significantly improved their operational skills and innovative capabilities. The innovative teaching model developed in this study not only aligns with the specific educational context of Xizang University but also provides an operational, replicable, and adaptable paradigm for reforming physics laboratory instruction in other remote-area institutions.